The Impact of Ownership Authority on Cash Conversion Cycle in Public Hospitals: A Comparative Analysis of Provincial and County Hospitals - Bartlomiej Krzeczewski (International Journal of Financial Studies)
(1) Background: The aim of the paper is to identify and assess if there are differences concerning the cash conversion cycle (CCC) according to different types of ownership authority of hospitals. The main research hypothesis developed for the purpose of this study assumes that the ownership authority is of great importance for the short-term financial management analyzed through the prism of the cash conversion cycle in hospitals. (2) Methods: A statistical hypothesis testing method is employed in the empirical part of the study, analyzing differences both in the values of the cash conversion cycle itself as well as in the values of its components, i.e., inventory conversion period, receivables conversion period, and payables conversion period. The research sample consists of public hospitals subordinated to different types of ownership authorities, i.e., provinces and counties. (3) Results: It turns out that there are indeed statistically significant differences between the provincial and county hospitals as far as the cash conversion cycle and its components are analyzed, which supports the research hypothesis. (4) Conclusions: The county hospitals are characterized by a better financial situation as compared to their provincial counterparts concerning CCC management.